Distribusi Dan Pemanfaatan Tanaman Kemukus(Piper Cubeba) Di Hutan Lindung RPH Sumbermanjing Kulon - Poegoeh Prasetyo Rahardjo; Gettik Andri Purwanti; Stephanus Meo Soa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
This cubeb research aims to determine the distribution and utilization of the cubeb plant in Sumbermanjing Kulon RPH. Observations of cubebs were carried out along plot 101 at Sumbermanjing Kulon RPH. This study used survey methods and direct observation in the field. This data collection technique used interpretation transects and 10 x 10 m plots. Construction of a 1000 m long observation transect line of cubeb (piper cubeba), then to determine the point of spread of cubeb (piper cubeba) using qualitative descriptive analysis. The data analysis technique used in this study is the Morisita index method. The Morisita Index (Id) is most often used to measure the distribution pattern of a species or population because the calculation results are not affected by differences in the mean value and the size of the sampling unit. The results showed that the distribution between cubebs was fairly even, although at some points the distribution of cubeb was not found, this was due to human or animal intervention which resulted in each span of distance.